Diterpenoids and Sesquiterpenoids from the Twigs and Leaves of Illicium majus - Fang, Zhen-Feng; Zhang, Gui-Jie; Chen, Hui; Bai, Jian; Yu, Shi-Shan; Liu, Yang; Wang, Wen-Jie; Ma, Shuang-Gang; Qu, Jing; Xu, Song (Planta Medica, 2013)
Four new abietane diterpenes (1–4) and two new cycloparvifloralone-type sesquiterpenoids (5–6) have been isolated from the twigs and leaves of Illicium majus, together with three known sesquiterpenoids and five known diterpenoids. Their structures were determined by spectroscopic analysis and chemical methods. The absolute configuration of the 15,16-diol moiety in 2 is confirmed by Snatzkeʼs method, observing the induced circular dichroism after the addition of dimolybdenum tetraacetate in DMSO. Compound 2 exihibited significant anti-inflammatory activity with an IC50 value of 0.26 ± 0.03 µM, while compounds 10, 11, and 13 showed good anti-inflammatory activities with IC50 values ranging from 1.94 ± 0.56 to 2.60 ± 0.48 µM.
Keywords: Illicium majus; Illiciaceae; abietane diterpenes; sesquiterpenoids; anti-inflammatory